An integrative examination of psychological distress and its nutritional and visual correlates among young adults in Ghana - Isaiah Osei Duah Junior; Wendy Ofori Asare; Elizabeth J. Johnson; Charllote Boateng; Hubert Osei Acheampong; David Ben Kumah; Kwadwo Owusu Akuffo (PLoS ONE, 2025)
Psychological distress is a key precursor to suicidal ideation during emerging adulthood, a period marked by increasing independence and responsibility. Despite this vulnerability, the prevalence and determinants of psychological distress among young adults in Ghana remain poorly understood. This study examined psychological distress and its lifestyle, dietary, visual, and cognitive correlates in 301 participants. Data on biographical, health, and physical activity factors were collected via structured questionnaires. Visual function was assessed objectively using LogMAR ETDRS charts and Pelli-Robson contrast sensitivity charts, and subjectively via the NEI-VFQ-25. Macular pigment optical density (MPOD) and dietary carotenoid intake were also measured. Cognitive function was assessed with a neuropsychological test battery, and psychological distress with the Kessler K10 scale. Ordinal logistic regression indicated that 23.3% of participants experienced psychological distress (14.6% mild, 3.0% moderate, 5.6% severe). Multivariate analyses showed that occasional alcohol consumption (AOR = 4.10, 95% CI: 1.63–10.12, p = 0.003) and longer swimming duration (AOR = 1.04, 95% CI: 1.01–1.09, p = 0.037) increased the odds of higher psychological distress severity, whereas higher VFQ–25 scores were protective (AOR = 0.95, 95% CI: 0.91–0.99, p = 0.008). Spending more than 50% of the day outdoors showed a marginal trend toward increased odds (AOR = 2.40, 95% CI: 0.97–5.81, p = 0.054). Other factors, including BMI, ethnicity, protective eyewear, and dietary carotenoids, were not significant after adjustment. These findings suggest that specific lifestyle and visual function factors influence the severity of psychological distress in young adults, whereas demographic, anthropometric, and most dietary factors appear less influential on the severity of psychological distress. Collectively, integrating substance use counseling, visual health support, and lifestyle interventions may help reduce psychological distress and promote mental wellbeing during emerging adulthood.